2019
DOI: 10.1101/19007971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing the deployment of ultra-low volume and indoor residual spraying for dengue outbreak response

Abstract: Recent years have seen rising incidence of dengue and large outbreaks of Zika and chikungunya, which are all caused by viruses transmitted by Aedes aegypti mosquitoes. In most settings, the primary intervention against Aedes-transmitted viruses is vector control, such as indoor, ultra-low volume (ULV) spraying. Targeted indoor residual spraying (TIRS) has the potential to more effectively impact Aedes-borne diseases, but its implementation requires careful planning and evaluation. The optimal time to deploy th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Fitting such entomological information to an agent-based model of Yucatan State, Mexico, showed that high levels of TIRS coverage (75% of houses treated once per year) applied preemptively before the typical dengue season (before July) could reduce DENV infections by 89.7% in year 1 and 78.2% cumulatively over the first 5 years of an annual program [32]. Such findings were confirmed with another modeling study comparing TIRS with indoor space spraying in Iquitos, Peru [33]. These findings suggest that preemptive TIRS may provide high short-term and long-term effectiveness in preventing ABVs in endemic areas where transmission is seasonal.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Fitting such entomological information to an agent-based model of Yucatan State, Mexico, showed that high levels of TIRS coverage (75% of houses treated once per year) applied preemptively before the typical dengue season (before July) could reduce DENV infections by 89.7% in year 1 and 78.2% cumulatively over the first 5 years of an annual program [32]. Such findings were confirmed with another modeling study comparing TIRS with indoor space spraying in Iquitos, Peru [33]. These findings suggest that preemptive TIRS may provide high short-term and long-term effectiveness in preventing ABVs in endemic areas where transmission is seasonal.…”
Section: Introductionmentioning
confidence: 58%
“…The doctor will be joined by one field team member, who will obtain demographic and behavioral data, and collect blood specimens. Acute and convalescent (obtained 28 [range [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] days after symptom onset) blood specimens will be collected from each suspected case to confirm ABV infection. Additionally, history of movement (by a retrospective movement survey) [16,52] will provide information on potential exposure locations for each case.…”
Section: Intervention Evaluationmentioning
confidence: 99%
“…During the past two decades, researchers have preserved mosquito specimens collected throughout the city of Iquitos (e.g. Cavany et al, 2020;Cromwell et al, 2017;Getis et al, 2003;Gunning et al, 2018;LaCon et al, 2014;Lenhart et al, 2020;Morrison et al, 2004a;Morrison et al, 2004b;Morrison et al, 2006;Morrison et al, 2008;Reiner et al, 2019;Schneider et al, 2004;Tun-Lin et al, 2009). Prior to 2002, no citywide insecticide spraying occurred.…”
Section: Entomological Surveysmentioning
confidence: 99%
“…9,10 Mathematical models also predicted strong and sustained reductions in Ae. aegypti and ABV transmission 11,12 and showed that greater epidemiological efficacy can be achieved as the insecticide residual efficacy increases. 13 TIRS expansion, adoption, and sustainability to the emergence of insecticide resistance will depend on the availability of insecticide molecules and formulations with high residual capacity and to which mosquitoes are susceptible.…”
Section: Introductionmentioning
confidence: 99%